Penerapan Manajemen Proyek Menggunakan Critical Path Method pada Awan Car Wash dan Cafe - Mahendra, Muhamad Oka; Sah Putra, Al Fiillian; Sudianto, Toto; Purnama, Yowarigo Putra; Fandi, Kiki Kris (Fakultas Teknik Universitas Tulang Bawang, 2025)
Project completion delays are a common problem that can affect the entire project work, to prevent delays, planning with several control devices is needed. Planning a project helps organizations understand the relationship between a project's activities and how they relate to the project as a whole, Awan Car Wash and Cafe experienced a significant surge in the number of customers, causing the existing capacity to be inadequate. One of the problems in the Awan Car Wash and Cafe laundry room is the limited washing capacity which causes long queues and longer service times. The purpose of the study was to obtain a critical path that could be used to plan the construction of the Awan Car Wash steam place in a structured and efficient manner. The research method used the Critical Path Method, The results of the study were that the construction project had a critical path duration of 19 weeks, this result was obtained before processing using the Critical Path Method, Based on data processing using the Critical Path Method, the critical path duration was 14 weeks. Periodic evaluation is highly recommended so that project progress continues to be monitored and problems can be addressed immediately before they develop. Keywords: Critical Path Method (CPM), Critical Path, Project Management, Project Scheduling